Peningkatan Kompetensi Siswa SMK Negeri 1 Bener Meriah Melalui Pelatihan Pengelasan Kanopi Untuk Dunia Usaha - Irwansyah; Syahirman Hakim; Hakim Muttaqim; Syifa Saputra; Wahyudi; Rustam Efendi; Hamdani (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The business world is an activity that includes the economy, including production, distribution, and other activities that aim to meet human needs and desires. Welding workshop services are one of the business sectors that continue to grow along with the increasing demand for security and aesthetics in buildings. The canopy functions as a protector from the heat of the sun and rain of a building. Therefore, it is important for welding workshop workers to have reliable skills and knowledge in making canopies. Community service activities aim to provide training and assistance on basic welding techniques on canopies that are useful for improving student competence. The method of activity carried out is a training technique with an allocation of theoretical and practical materials related to the basics of SMAW welding and welding on canopies which are attended by students of the Welding Engineering and Metal Fabrication Department, SMK Negeri 1 Bener Meriah. The results of the activity are as follows: can provide skills for vocational school students to enter the world of work related to the competence of operating SMAW welding machines correctly and can also connect plates on canopy construction using SMAW welding. The results of the material absorption of the student post-test showed a competence of 82%, this shows that students have gained welding skills on canopies and they hope that next year there will be a follow-up program.